Stability Assessment of a Bedding Rock Slope Using Q-slope and Seismic Tomography: A Case Study in the Ecuadorian Amazon - Espin, Jorge Ronny (2022)
Roads are generally affected by slope failures, and these failures can increase when there are weathered materials and high rainfall. These circumstances occur in the sub-Andean zone of Ecuador. This is the region where the study area is located. The stability of a stratified rock slope, which is affecting a section of highway E45, was evaluated. The study slope is exposed to the road, but the upper part is covered by a soil-type material and dense vegetation that makes it challenging to study. We applied the Q-slope method and seismic tomography; these methods used together worked well, because they allowed to correlate and infer information about the quality of the rock mass, even in a fast and economical way. We also performed core drilling with core recovery in the crown of the slope and SPT test. The slope presented two well-differentiated zones; therefore, Q-slope values were calculated for each of these zones. The results show that the slope is unstable. The application of seismic tomography as an input parameter for calculating Q-slope was important because it allowed evaluating the stability where it is impossible to collect geomechanical information, correlate information taken at the foot of the slope, and define the depth of the bedrock.